Idea pembangunan “R.A.H.M.A.N” dari perspektif Lee Kuan Yew - Jaes, Lutfan; Abdul Aziz, Abdul Rahman (Universiti Tun Hussein Onn Malaysia, 2013)
Lee Kuan Yew (LKY) is superior statesman with the pragmatic and effective leadership style to achieve the vision in the develop mentalist country.Nearly 60 years (1955-2011) of experience made him as unchallenged political leaders in Singapore even Southeast Asia.His leadership ability has been successful to led the Singapore community thrive.He led to developed after Singapore separated by Malaysia. History of the Malaya cannot be separated by this character. He was a "hardcore troublemakers" while in the Malaysian parliament.“Malaysian Malaysia” concept introduced by him is troubling for the late Tunku Abdul Rahman and Tun Abdul Razak in Perikatan. Tun Dr. Mahathir, has always been a "hero" to deflect LKY brilliant didactic arguments.LKY resigned as prime minister in 1990 but appointed as a Senior Minister (1990-2004) and Minister Mentor (2004-2011). This allows him to still relevant in the Singapore political arena.It makes his leadership keep across the centuries.His perspective is not only limited to the development of Singapore but even to the particularly Malaysia and Southeast Asia.Therefore this paper tries to look the developments of idea and leadership style of the six (6) Prime Minister of Malaysia; namely R.A.H.M.A.N by LKY. Through different view, perhaps the ideas of the Prime Minister's legacy be obtained for the future.